Posttranscriptional Gene Regulation of T Follicular Helper Cells by RNA-Binding Proteins and microRNAs - Baumjohann, Dirk; Heissmeyer, Vigo (Frontiers in Immunology, 2018)
T follicular helper (Tfh) cells are critically involved in the establishment of potent antibody responses against infectious pathogens, such as viruses and bacteria, but their dysregulation may also result in aberrant antibody responses that frequently coincide with autoimmune diseases or allergies. The fate and identity of Tfh cells is tightly controlled by gene regulation on the transcriptional and post-transcriptional level. Here, we provide deeper insights into the post-transcriptional mechanisms that regulate Tfh cell differentiation, function and plasticity through the actions of RNA-binding proteins and small endogenously expressed regulatory RNAs called microRNAs. The Roquin family of RNA-binding proteins has been shown to dampen spontaneous activation and differentiation of naïve CD4+ T cells into Tfh cells, since CD4+ T cells with Roquin mutations accumulate as Tfh cells and provide inappropriate B cell help in the production of autoantibodies. Moreover, Regnase-1, an endoribonuclease that regulates a set of targets that strongly overlap with those of Roquin, is crucial for the prevention of autoantibody production. Interestingly, both Roquin and Regnase-1 proteins are cleaved and inactivated after TCR stimulation by the paracaspase MALT1. Similarly, microRNAs are expressed in naïve CD4+ T cells and help preventing spontaneous differentiation into effector cells. While most microRNAs are downregulated upon T cell activation, several microRNAs have been shown to regulate the fate of these cells by either promoting (e.g. miR-17∼92 and miR-155) or inhibiting (e.g. miR-146a) Tfh cell differentiation. Together, these different aspects highlight a complex and dynamic regulatory network of post-transcriptional gene regulation in Tfh cells that may also be active in other T helper cell populations, including Th1, Th2, Th17, and Treg.